2020
DOI: 10.1016/j.tem.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Manifestations and Mechanisms in Patients with COVID-19

Abstract: COVID-19 patients with preexisting cardiovascular diseases or with cardiovascular complications have showed a higher risk of mortality. The main cardiovascular complications of COVID-19 include acute cardiac injury, acute myocardial infarction, myocarditis, arrhythmia, heart failure, shock, and venous thromboembolism/pulmonary embolism. COVID-19 could cause cardiovascular complications or deterioration of coexisting cardiovascular diseases through direct or indirect mechanisms, including viral toxicity, dysreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 126 publications
2
57
0
11
Order By: Relevance
“…The primary route of entry for SARS-CoV-2 are the airway epithelial cells, after which it migrates to the lung alveolar epithelial cells, where it rapidly replicates and triggers a massive immune response called the "cytokine storm, " leading to "ARDS" and respiratory failure (4-7). The surface receptor that SARS-CoV-2 uses for cellular entry, the ACE2, is widely present in all cell types, including endothelial cells (EC) of small resistance arteries (20)(21)(22). Available evidence suggests COVID-19 causes severe vascular damage by disrupting endothelial function (1,(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…The primary route of entry for SARS-CoV-2 are the airway epithelial cells, after which it migrates to the lung alveolar epithelial cells, where it rapidly replicates and triggers a massive immune response called the "cytokine storm, " leading to "ARDS" and respiratory failure (4-7). The surface receptor that SARS-CoV-2 uses for cellular entry, the ACE2, is widely present in all cell types, including endothelial cells (EC) of small resistance arteries (20)(21)(22). Available evidence suggests COVID-19 causes severe vascular damage by disrupting endothelial function (1,(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact pathophysiological mechanisms underlying myocardial injury induced by COVID-19 remain to be fully elucidated. The possible mechanisms include the direct damage to cardiomyocytes of SARS-CoV-2 infection through angiotensin-converting enzyme 2, cytokine storm precipitated by overactivation of the immune response, dysregulation of the renin–angiotensin–aldosterone system, and disturbances of coagulation and microcirculation-induced hypoxia ( 3 , 5 , 25 ). A previous study revealed a critical role of SARS-CoV in transforming growth factor β signaling, which is a predominant regulator of cardiac fibrosis ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated 18% incidence of cardiovascular events and carried 45.2% mortality rate in this metropolitan sample population cohort. COVID-19 can cause cardiovascular complications or deterioration of coexisting cardiovascular diseases through direct or indirect mechanisms, including viral toxicity, dysregulation of the renin–angiotensin–aldosterone system, endothelial cell damage and thromboinflammation, cytokine storm, and oxygen supply–demand mismatch 24 , 25 . Published clinical studies suggested COVID-19 itself might induce myocardial injury, arrhythmia, acute coronary syndrome, and venous thromboembolism 5 , 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%